PENDEKATAN KOLABORATIF DALAM PENGELOLAAN DAERAH ALIRAN SUNGAI CITARUM - Raharja, Sam’un Jaja (Bumi Lestari; Vol 10 No 2 (2010), 2010)
Untintegrated management and complicated factors lead to problem in Citarum watershed management. The main problems of the research are the management of Citarum’s watershed has been fragmented and conflict among stakeholders. There is need a new concept and approach for managing Citarum watershed so that management of Citarum Watershed more effective. The base proposition of research is Citarum watershed management requires a concept about cooperation among stakeholders than can settle the conflict among them as consequence of fragmented-sectoral management. Based on research analysis, this research formulated some finding. Citarum watershed management are independent, it caused the absence of an institution which functions as leader. Relationship among organizations is ill-structured, caused by overlapping role and function among them. The most appropriate collaboration model for Citarum Watershed management is interdependent model. Research recommendation to rearrangement core task and function of organization base in term collaborative governance.
Keywords: management, watershed, collaboration, task and function